Technology’s influence on Pentecostalism: Shaping perception and religious impact - Mudau, Ndidzulafhi; Tshifhumulo, Rendani (African Journal of Pentecostal Studies, 2025)
BackgroundThe advancement of media and technology has significantly influenced religious expression, particularly among Pentecostals, facilitating novel engagement methods, outreach and worship.ObjectivesThe study’s setting is global, investigating how contemporary Pentecostalism mediates between traditional and digital religious expressions through various media formats, including social media, live streaming and multimedia worship performances.MethodUtilising a literary research methodology focused on modern literature, media and technological themes associated with Pentecostalism. Data were collected from scholarly journal articles, church publications, internet sermons, social media posts and films. This was executed to provide a comprehensive overview.ResultsThe results indicate that Pentecostal leaders adeptly utilise modern media to enhance religious participation in compelling manners, expanding worldwide outreach while preserving local ties. Media channels allow churches to meet contemporary societal demands by promoting theological education, evangelism and community building beyond geographical boundaries.ConclusionAlthough media and technology provide novel avenues for worship, foster theological innovation and facilitate global development, concerns arise regarding the authenticity of the worship experience, the influence on established traditions and the marginalisation of individuals lacking technological proficiency.ContributionThis study enhances comprehension of the interplay between Pentecostalism and digital media, offering insights for religious leaders seeking to incorporate technology while preserving their theological principles. It establishes a foundation for future enquiries into how religious communities may leverage technology’s potential while recognising its constraints in spiritual contexts.